Construction of t-way covering arrays using genetic algorithm - Sabharwal, Sangeeta; Bansal, Priti; Mittal, Nitish (International journal of system assurance engineering and management, 2017)
In a component based system, interaction among components may give rise to interaction faults. Faults can be caused by the interactions of two or more than two components. Since, it is not feasible to test all possible interactions combinatorial interaction testing is being employed to generate covering arrays (CAs) that covers all t-way interactions between components. In this paper, we generalize our previous work, that uses a greedy based genetic algorithm, to generate CA from 2-way to t-way testing (2 ≤ t ≤ 4). We implement the proposed strategy by extending an open source tool PWiseGen. The main drawback of PWiseGen is the need to input the size of CA in advance. To overcome this restriction of PWiseGen, we propose a variation of binary search algorithm that generates optimal CA without knowing its size in advance. Experiments are conducted to evaluate the effectiveness of the proposed approach and it has been observed that the proposed approach performs well as compared to existing state-of-the-art algorithms.